Injecction of trigger points in the temporal muscles of patients with miofascial syndrome - Svetlana Sabatke; Rosana Herminia Scola; Eduardo S. Paiva; Pedro André Kowacs (Arquivos de Neuro-Psiquiatria)
Objective : The aim was to examine the effect of blocking trigger points in the temporal muscles of patients with masticatory myofascial pain syndrome, fibromyalgia and headache.Method : Seventy patients with one trigger point were randomly divided into 3 groups: injection with saline or anesthetic and non-injected (control).Results : Pain was reduced in 87.71% patients injected with saline and 100% injected with anesthetic. Similar results were obtained for headache frequency. With regard to headache intensity, the injection groups differed from the control group, but not between themselves.Conclusion : Treatment with injection at trigger points decreased facial pain and frequency and intensity of headache. Considering the injected substance there was no difference.